2013
DOI: 10.1111/jse.12046
|View full text |Cite
|
Sign up to set email alerts
|

Plant sexual systems correlated with morphological traits: Reflecting reproductive strategies of alpine plants

Abstract: Plant sexual systems can be affected by various environmental factors, and thus show a range of morphological differences. The associations between plant sexual systems and morphology are unique, for example, the subnival belt of the Hengduan Mountains has harsh climatic conditions, but hosts remarkable biodiversity. However, these associations have received surprisingly little attention. We analyzed the associations in this region, and compared the pattern of sexual systems with that of other floras, and we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 55 publications
3
40
1
1
Order By: Relevance
“…Since low stature is a common adaptation in alpine species (Billings ; Fabbro & Körner ; Peng et al. ), lower plant height of alien species occurring at higher elevations is in line with the predictions of the ALH.…”
Section: Discussionsupporting
confidence: 58%
“…Since low stature is a common adaptation in alpine species (Billings ; Fabbro & Körner ; Peng et al. ), lower plant height of alien species occurring at higher elevations is in line with the predictions of the ALH.…”
Section: Discussionsupporting
confidence: 58%
“…Solar radiation may affect the relative representation of sexual systems via its influence on flower coloration (Peng et al, 2014). For example, Peng et al (2014) found that hermaphroditism was significantly associated with showy flower colour in alpine plants. Quantifying the influence of solar radiation on the frequency of different sexual systems via flower coloration deserves further study.…”
Section: Influence Of Climate On the Proportions Of Sexual Systemsmentioning
confidence: 99%
“…In both annuals and perennials, autonomous selfing was found to have provided reproductive assurance under pollinator scarcity (e.g., Zhang & Li, ; Duan et al, ), even under strong inbreeding depression (Zhang et al, , ). In the subnival region of the SE QTP, more than 85% of the total number of species are hermaphroditic, likely favoring selfing when pollinators are unavailable (Peng et al, ).…”
Section: Tentative Summaries Of Recent Advancesmentioning
confidence: 99%